Emotional Intelligences Influence on Confrontation Resolving Skills of Principals at School Administration - Mariyadas, Shandru; Saravanakumar, AR. (Interdisciplinary Social Studies, 2023)
Background: School consists of complex network of social relations, built and maintained by bridging the gap between significant behavioral modifications. The quality of these relations defines the organizational culture. Thus, administrative atmosphere depends upon social skills as communication, attitude and response of their co-worker. Aim: The purpose of this study was to observe the relationship between school principal’s emotional intelligence and confrontational resolving skills. Method: Partial correlation was conducted to survey the degree of relationships between principal’s emotional intelligence and confrontational resolving skills for the effect of school as an administration, Data analysis was utilized to examine the combined effect of principal’s emotional intelligence quotient and confrontational resolving skills on principal’s achievement. The study population consisted of 72 school principals and 732 teachers within Batticaloa District schools in Sri Lanka. Quantitative data were collected and openly available consistent test pass percentage data. Findings: The data examination using SPSS and MS Excel showed that the principals have a very high or a high emotional intelligence and they generally use collaborating style of conflict resolution. Emotional Intelligence (EI) and conflict resolution styles (CRS) are 75% related with each other.